X-Ray and Ultrasonography in Forearm Trauma. Issue 6 (November 2015) - Tandogan, M; Katirci, Y; Sonmez, F Turan; Duymaz, H; Altun, S; Gunaydin, YK; Coskun, F
Introduction: This study aimed to prevent unnecessary exposure to ionising radiation, and to exclude non-fracture cases in children admitted to the emergency department with a forearm trauma, by showing that forearm trauma could be assessed with ultrasonography (USG) as accurately and precisely as with direct radiography. Methods: A total of 105 patients (67 males and 38 females) were included in the study. Before performing radiography, the patients were assessed with USG and the results were recorded. The findings of USG and radiography were then compared. Results: A total of 58 (55%) patients had fractures detected with USG. When compared to X-ray, the sensitivity of USG in detecting forearm fractures was 98.3% (95% confidence interval [CI]: 90.7-100%), specificity was 95.8% (95% CI: 86.0-98.9%), negative likelihood ratio was 0.018, positive likelihood ratio was 23.58, negative predictive value was 97.9% (95% CI: 88.7-99.9%), and positive predictive value was 96.6% (95% CI: 88.1-99.6%). Conclusion: The use of USG on selected cases of paediatric patients may provide a more rapid evaluation so as to reduce exposure to ionising radiation. We believe that USG will be useful in excluding non-fracture cases. (Hong Kong j.emerg.med. 2015;22:352-358)